Electromagnetic characterization of a new metamaterial resonator for microwave applications - BERKA Mohammed; MAHDJOUB Zoubir; BENDAOUDI Amina (University Of Eloued جامعة الوادي, 2020)
A characterization of a new metamaterial resonator is presented in this work. The studied structure is a symmetrical split rings resonator (SSRR) for square shape and magnetic activity. Two different configurations of (SSRR) are proposed to show the influence of the geometric shape on the electromagnetic qualities of the chosen metamaterial. The two resonators for the two proposed configurations (SSRR1) and (SSRR2) are formed by two square rings; inner and outer which are etched on the upper face of a dielectric substrate of FR4_Epoxy. The obtained results by simulations based on the HFSS simulator show the influence of the geometric shape on the reflection, transmission, refractive index and the absorption of the studied metamaterial resonator.
Intervention
Keywords: absorption; metamaterial; reflection; resonator; transmission.